Interpersonal Problems in Social Anxiety Disorder Across Different Relational Contexts - Tonge, Natasha A. (J Anxiety Disord, 2020)
People with social anxiety disorder (SAD) frequently report interpersonal problems across various domains; however, it is unclear whether these problems are observable by others or represent negatively biased self-report. We assessed the interpersonal problems of people with and without SAD using self-report, friend, and romantic partner report. We hypothesized that SAD diagnosis would predict self-reported problems across multiple interpersonal domains, but restricted domains of informant report. Additionally, we hypothesized that diagnosis would predict discrepancy between self and informant report either in the form of a bias toward reporting more problems or in the form of lack of concordance between self and informant reporters. Using structural equation and multilevel models, we found evidence for differences between people with and without SAD in terms of domains of impairment observed by self and informants as well as differences in correspondence across relationship types. Results highlight the utility of multi-informant assessment of SAD.